Tackling Bribery in Indonesian Private Sector - Rachman, Taufik; Hidayat, Ilham; Wibisono, Didan; Muhammad, Farhan (Center for Law and Responsible Business Studies, 2026)
Corruption poses a formidable barrier to global socioeconomic progress and is a critical impediment to development which undermines the rule of law and hampers institutional frameworks crucial for economic growth. Its pervasive influence extends across various sectors, encompassing utilities, healthcare, education, and even national security domains. In Indonesia, corruption remains entrenched despite efforts such as the establishment of the Corruption Eradication Commission (KPK) in 2002. While primarily targeting public sector corruption, Indonesian law must also address instances in the private sector, which constitutes a significant portion of corrupt activities. This paper is motivated by not only Indonesia’s international commitment to the UNCAC, but also the evidently adverse impacts on private sector bribery to the Indonesian economy. Not to mention, the shortcomings of Indonesia’s current framework to address this type of bribery. In doing so, it is of the view that lessons can be learned from other jurisdictions, namely: Singapore, Hong Kong and the Netherlands. This paper suggests expanding legal provisions to encompass private sector bribery, solicitation, and indirect bribery, this is tailored to Indonesia’s socio-cultural context.